Telework-related risk factors for musculoskeletal disorders - Milaković, Marina; Koren, Helena; Bradvica-Kelava, Karmen; Bubaš, Marija; Nakić, Josipa; Jeličić, Pavle; Bucić, Lovro; Bekavac, Barbara; Čvrljak, Jelena; Capak, Magdalena (Frontiers in Public Health, 2023)
Telework has become considerably more common during the pandemic. Although working remotely has numerous advantages, negative impacts on workers’ health should also be considered. Telework is a major contributor to the development or aggravation of work-related musculoskeletal disorders where unsuited workstation ergonomics, sedentary behavior, as well as psychosocial and organizational factors seem to play a role. This paper aims to identify telework-related risks and their impact on musculoskeletal health as well as provide recommendations that may be useful in constructing preventive measures. A comprehensive literature search has been performed. Poor ergonomic solutions when it comes to workstation design resulting in prolonged sitting in non-neutral positions contribute to the development/aggravation of musculoskeletal disorders in teleworkers. Working with inadequately placed screens and laptops and sitting in maladjusted seats without usual functionalities and ergonomic support is associated with musculoskeletal discomfort. Extended working hours with fewer rest periods to meet increased work demands, social isolation, and lack of support from work colleagues and superiors as well as blurred work-home boundaries and omnipresence of work are commonly stated psychosocial and organizational factors associated with musculoskeletal disorders. Environmental factors such as poor lighting and glare, inadequate room temperature, and ventilation or noise, are frequently overlooked remote workstation risk factors. For a certain part of workers, telework will remain a common way of work in the post-pandemic period. Therefore, it is essential to identify telework-related risk factors for musculoskeletal disorders and address them with timely preventive measures tailored to each remote workstation’s risks and individual workers’ needs.